Pengembangan Trainer Sensor Pada Mata Pelajaran Sensor Dan Aktuator Kelas XI Jurusan Teknik Elektronika Industri Di SMK Sunan Drajat Lamongan - Jariyah, Ainun; Suryono, Suryono (Electrical Engineering, Universitas Negeri Semarang, 2020)
AbstractÃ¢â‚¬â€ Subjects of censorship and actuators in the Industrial Elektronics Departement SMK Sunan Drajat Lamongan have no learning media, during the learning process of sensor subjects and actuators only with media lectures without the presence of theaching aids such as trainers. From the problem, the researcher then made an integrated and feasible sensor trainer used as a learning media on the subjects of sensors and actuators to improve students understanding. The research method used in this study is Reseach and devolepment (R&D). Products made in the form of sensor trainer learning media consisting of a potentiomer sensor, optocoupler speed sensor, DHT11 temperature and humadity sensor, MQ-7 gas sensor, FSR load sensor, proximity sensor. The testing stage includes expert media testing and product testing. The resultd of the analysis of media expert data obtained a percentage of feasibility of 84,67% with a very valid category and the results of product trials of 0,72 with a high category in the N-Gain category. The results of testing of the position sensor, speed, temperature and humidity, gas, load, and proximity have been calibrated according to the actual conditions. Based on the results of the study, it can be concluded that the learning media of sensor trainers is feasible to be used as learning media on the subjects of sensors and actuators because they are considered to be able to improve students understanding of various sensors and their working principle. The researcher gives suggestions to the next researcher, namely : (1) develop reaseach with other sensors and add the application again, (2) make this researcher as a reference material for feature research. KeywordÃ¢â‚¬â€ sensor trainers, learning media, sensors and actuators.